2014
DOI: 10.3791/52200
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Ascending Aortic Stiffness <em>In Vivo</em> in Mice Using Ultrasound

Abstract: We present a protocol for measuring in vivo aortic stiffness in mice using high-resolution ultrasound imaging. Aortic diameter is measured by ultrasound and aortic blood pressure is measured invasively with a solid-state pressure catheter. Blood pressure is raised then lowered incrementally by intravenous infusion of vasoactive drugs phenylephrine and sodium nitroprusside. Aortic diameter is measured for each pressure step to characterize the pressure-diameter relationship of the ascending aorta. Stiffness ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Previous research on humans and animals indicated that arterial elasticity is linked to the structural arrangements of the artery 38 relating to cardiovascular disease and aging. 38,39 Preclinical studies showed that arterial elasticity decreases during fatty streak formation, before pathophysiological changes. 38 Leone et al concluded that carotid artery distension is an independent predictive marker of coronary heart disease in the elderly and found that carotid artery distension was associated with carotid plaque burden.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on humans and animals indicated that arterial elasticity is linked to the structural arrangements of the artery 38 relating to cardiovascular disease and aging. 38,39 Preclinical studies showed that arterial elasticity decreases during fatty streak formation, before pathophysiological changes. 38 Leone et al concluded that carotid artery distension is an independent predictive marker of coronary heart disease in the elderly and found that carotid artery distension was associated with carotid plaque burden.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the aforementioned in vivo metrics of arterial stiffness, such as PWV (either determined though Doppler measurements, 43, 44 applanation tonometry, 45 or MRI 46 ) or local arterial compliance and distensibility 25, 47, 48 have been established for use in murine studies. Those methods are indispensable for longitudinal in vivo studies measuring arterial stiffness but only allow indirect assessment of biomechanical properties.…”
Section: Physiological Arterial Compliance and Assessment Of Arterialmentioning
confidence: 99%
“…However, the PWV is usually measured from the carotid-femoral artery PWV, a global index, which does not reflect local stiffness variations. In theory, aortic stiffness could be estimated directly, by measuring with US the aorta pulsatility under a known pressure variation (systo-diastolic) (55), in different aortic segments (56). Whether segmental aortic stiffness measured by US might discriminate different patients' conditions and risk, it is worth exploring.…”
Section: Current and Future Applicationsmentioning
confidence: 99%